Prevalence and molecular characterization of amikacin resistance among Mycobacterium tuberculosis clinical isolates from southern China. (September 2020) - Islam, Md Mahmudul; Tan, Yaoju; Hameed, H.M. Adnan; Liu, Yang; Chhotaray, Chiranjibi; Cai, Xiaoyin; Liu, Zhiyong; Lu, Zhili; Wang, Shuai; Cai, Xingshan; Su, Biyi; Li, Xinjie; et al.
Highlights: Amikacin is only considered for multidrug-resistant tuberculosis (MDR-TB) treatment when a short MDR-TB regimen is designed. The rrs mutations were found in 82% of amikacin-resistant isolates in southern China. The A1401G mutation in the rrs gene was the most dominant mutation in amikacin-resistant isolates. Analysis of rrs gene mutation will significantly reduce the time and cost to diagnose amikacin resistance. Notably, 13.48% amikacin-resistant isolates had no known mutation in rrs, eis, tap and whiB7 . Abstract: Objectives: Amikacin is the only second-line injectable antituberculosis (anti-TB) drug still recommended for multidrug-resistant tuberculosis (MDR-TB) treatment when a short MDR-TB regimen is designed. Mutations in rrs and eis are reported to be associated with resistance to amikacin. In this study, we investigated the incidence of rrs, eis, tap and whiB7 mutations in amikacin-resistant Mycobacterium tuberculosis clinical isolates to find the proportion of different mutations related to amikacin resistance. Methods: A total of 395 clinical isolates of M. tuberculosis were used for phenotypic drug susceptibility testing (DST) to 10 drugs with the Löwenstein–Jensen (L–J) method. We sequenced rrs, eis, tap and whiB7 genes in 178 M. tuberculosis clinical isolates (89 amikacin-resistant isolates and 89 of 306 amikacin-susceptible isolates). Results: Our data showed that 22.53% (89/395) M. tuberculosis clinical isolates were resistant to amikacin. Of the 89 amikacin-resistant isolates, 89.89% (80/89) were MDR-TB, of which 12.36% (11/89) were pre-extensively drug-resistant TB (pre–XDR-TB) and 77.53% (69/89) were XDR-TB. The rrs mutations were found in 82% (73/89) in amikacin-resistant M. tuberculosis clinical isolates. The A1401G alteration in the rrs gene was the most dominant mutation (80.90%; 72/89). Five mutations were detected as new in rrs, tap and whiB7 . Notably, 13.48% (12/89) amikacin-resistant isolates had no known mutation in these genes. Conclusions: Our data reveal that the rrs mutation is a predominant molecular marker of amikacin resistance in southern China. Analysis of the rrs gene mutations will significantly reduce the time and cost to diagnose amikacin resistance in TB patients. Other unknown amikacin resistance mechanism(s) exist.